Crystal and cryoEM structural studies of a cell wall degrading enzyme in the bacteriophage φ29 tail - Xiang, Ye (National Academy of Sciences, 2008)
The small bacteriophage φ29 must penetrate the ≈250-Å thick external peptidoglycan cell wall and cell membrane of the Gram-positive Bacillus subtilis, before ejecting its dsDNA genome through its tail into the bacterial cytoplasm. The tail of bacteriophage φ29 is noncontractile and ≈380 Å long. A 1.8-Å resolution crystal structure of gene product 13 (gp13) shows that this tail protein has spatially well separated N- and C-terminal domains, whose structures resemble lysozyme-like enzymes and metallo-endopeptidases, respectively. CryoEM reconstructions of the WT bacteriophage and mutant bacteriophages missing some or most of gp13 shows that this enzyme is located at the distal end of the φ29 tail knob. This finding suggests that gp13 functions as a tail-associated, peptidoglycan-degrading enzyme able to cleave both the polysaccharide backbone and peptide cross-links of the peptidoglycan cell wall. Comparisons of the gp13(−) mutants with the φ29 mature and emptied phage structures suggest the sequence of events that occur during the penetration of the tail through the peptidoglycan layer.